Advantages of Using Information Technologies in Primary School Mathematics - Jonpolatovna, Saidova Mokhinur; Gulomovna, Ubaydullaeva Sharofat (European Journal of Life Safety and Stability (2660-9630), 2021)
The article reflects the advantages of information technology, methods of their use, the effectiveness and use of modern information and communication technologies in primary school mathematics lessons. It is noted that the lessons organized on the basis of information technology are based on the improvement of the education system.